Teledermatology in Times of COVID-19 Pandemic - Daniel Henry; David Henry (Nepal Journal of Dermatology, Venereology & Leprology)
Teledermatology is the need of every dermatologist in the time of COVID-19 pandemic. Teledermatology will help to provide skin care to the patients in the time of pandemic and will also help to prevent the spread of COVID infection.